A sustentabilidade como estratégia no cooperativismo: um estudo de caso único sobre as práticas estratégicas de sustentabilidade em uma cooperativa de crédito brasileira - Santos, William Neves dos (Universidade do Vale do Rio dos Sinos, 2021)
The sustainability agenda isn’t new in the corporate environment, it is already considered an imperative theme for organizational strategies. In cooperatives, this reality is no different, especially because of the connection between the concepts of cooperativism and sustainability. However, it is necessary to understand how a sustainability strategy is developed, considering the singularities of a cooperative organization. In order to shed light on this issue, this exploratory study, with a qualitative approach, aims to analyze the strategic sustainability practices of a credit cooperative that stands out in the Brazilian scenario and propose a framework for the sustainable development of cooperatives. To this end, a single case study was carried out, with a credit cooperative of national prominence regarding the theme of sustainability, the data collection occurred through documentary research, observation and semi-structured interviews carried out with actors directly involved with the theme in the cooperative. Through the Strategy as Practice approach, the sustainability strategy was analyzed and data collection took place through documentary research, observation and semi-structured interviews carried out with actors directly involved with the theme in the cooperative. Afterwards, with the content analysis technique, the data were triangulated. It was identified that the cooperative deals with the sustainability theme as a strategic factor for the organization and follows a market orientation, thus developing a wide range of practices that make sustainability a transversal theme in the cooperative. The role of senior leadership and the tactical level manager for disseminating the topic throughout the organization was highlighted, as well as the educational effort with employees on the topic. The lack of awareness about sustainability, by most members, was an identified point of attention. The results demonstrate that, despite the important relationship between cooperativism and sustainability, it is necessary for the cooperative to have strategies based on market practices and the demands of local communities, as well as a flow of activities that allow the cooperative to learn and adapt quickly. Furthermore, a framework was built as a synthesis of the results of this study. Finally, this study expands the research line of Marketing and Global Markets, bringing not only managerial contributions to cooperatives, but also theoretical contributions to advances in the field of research on sustainability and cooperatives.
Keywords: Cooperativas; Sustentabilidade; Estratégia como prática; Cooperatives; Sustainability; Strategy as practice; ACCNPQ::Ciências Sociais Aplicadas::Administração